2006
DOI: 10.1016/j.stam.2006.11.014
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional nanomaterials synthesized using high-energy ball milling and annealing process

Abstract: One-dimensional (1D) nanomaterials including nanotubes, nanowires and nanorods have many new properties, functionalities and a large range of promising applications. A major challenge for these future industrial applications is the large-quantity production. We report that the ball milling and annealing process has the potential to achieve the mass production. Several examples including C, BN nanotubes and SiC, Zn nanowires are presented to demonstrate such capability. In addition, both size and structure of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Therefore, conventional ball milling system cannot be used directly to conduct any HEBM work and specially designed ball mills with a higher milling energy are preferred for HEBM. 43 Lattice relaxation of ZnO in z direction observed in our study has also been reported by a number of workers. For example, Bao et al 44 reported on the observation of slightly higher c values for ZnO thin films prepared on quartz glass substrates by sol-gel method.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, conventional ball milling system cannot be used directly to conduct any HEBM work and specially designed ball mills with a higher milling energy are preferred for HEBM. 43 Lattice relaxation of ZnO in z direction observed in our study has also been reported by a number of workers. For example, Bao et al 44 reported on the observation of slightly higher c values for ZnO thin films prepared on quartz glass substrates by sol-gel method.…”
Section: Discussionsupporting
confidence: 89%
“…Obtaining nanoparticles of ZnO in this size (30 nm) is a remarkable result, maybe due to the use of the high-energy ball milling technique. Other investigators have reported 41,43 that when the particles become small enough (typically hundreds of nm), further refinement cannot be observed due to equilibration of cold welding and fracturing. In these cases, this might be due to the use of the conventional ball milling technique, which is different from the high-energy ball milling used in our study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Chen and co-workers [14] have produced carbon nanotubes using HEBM. They used graphite as precursor and milled it for about 150 h at ambient temperature, followed by a heat treatment at 1,400 °C for 6 h in a nitrogen atmosphere.…”
Section: Nanotubes and Nanowiresmentioning
confidence: 99%
“…Barium hexaferrite was doped with foreign substances, and the changes on the properties of the materials were investigated. They discovered the relationship between the synthesis method and the properties of the materials [8,9]. In their studies, they found the method to optimize the magnetic properties of barium ferrite.…”
Section: Introductionmentioning
confidence: 99%